Prospecção farmacológica etnodirigida de plantas medicinais com efeito gastroprotetor em comunidades rurais do município de Areia Branca/SE - Jesus, Ana Marta Libório de (2016)
The peptic ulcer is a chronic health problem of great social magnitude, which results from an imbalance between protective factors and harmful factors present in the mucosa of the gastrointestinal tract. With the advent of endoscopy and the discovery of the Helicobacter pylori´s bacteria, its treatment has undergone major changes. Currently, a great variety of drugs is available on the market for the treatment of this pathology. However, the conventional drug treatment is expensive making it inaccessible to the poorest populations. Moreover, many pharmaceutical products in use are not fully effective and can cause serious side effects when used for long period. For these reasons, the use of natural products of plant origin is an alternative to conventional therapy. In this sense, Ethnobotany and Ethnopharmacology have often been used by many scientists as the primary approach in the search for plant species with herbal properties. In rural communities, medicines plants represent one of the few therapeutic resources available to the population and are used in the healing process and maintenance of physical and/or spiritual. Given these arguments, this research had as main objective the achievement of an ethno-oriented study in order to identify medical plants with gastroprotective effects in four rural communities in the Areia Branca city in the Sergipe state. In the development phase of this research was initially carried out ethnopharmacological survey of local experts (holders of popular knowledge about medicinal plants) residing in Povoado Areias, Canjinha, Junco and Rio das Pedras. This survey permitted the identification of 14 plant species used in these communities for the treatment of gastrointestinal ulcers. Among these, the species Costus spiralis (Jacq.) Roscoe, Hyptis pectinata (L.) Poit. and Plectranthus barbatus Andr. were selected for assessment of antiulcer activity in animal model. Afterwords, the botanical material was collected on site and the crude aqueous extracts was prepared from the part of the plant used in folk medicine. The gastroprotective effect of selected plants to study was evaluated by the method of ethanolinduced gastric ulcer in Wistar rats. From the proposed experiment, it was found that all tested plants have gastroprotective effect and the Costus spiralis (Jacq.) Roscoe was the most effective and the Plectranthus barbatus Andr., the most potent. Thus, in addition to promoting the rescue and preservation of popular knowledge about the medicinal flora, this study provides scientific contribution to the popular use of these medicinal plants.